Kinetic Studies on Fermentative Production of Biofuel from Synthesis Gas Using Clostridium ljungdahlii - Maedeh Mohammadi; Abdul Rahman Mohamed; Ghasem D. Najafpour; Habibollah Younesi; Mohamad Hekarl Uzir (The Scientific World Journal)
The intrinsic growth, substrate uptake, and product formation biokinetic parameters were obtained for the anaerobic bacterium, Clostridium ljungdahlii, grown on synthesis gas in various pressurized batch bioreactors. A dual-substrate growth kinetic model using Luong for CO and Monod for H2 was used to describe the growth kinetics of the bacterium on these substrates. The maximum specific growth rate (μmax = 0.195 h−1) and Monod constants for CO (Ks,CO = 0.855 atm) and H2 (Ks,H2 = 0.412 atm) were obtained. This model also accommodated the CO inhibitory effects on cell growth at high CO partial pressures, where no growth was apparent at high dissolved CO tensions (PCO∗>0.743 atm). The Volterra model, Andrews, and modified Gompertz were, respectively, adopted to describe the cell growth, substrate uptake rate, and product formation. The maximum specific CO uptake rate (qmax = 34.364 mmol/gcell/h), CO inhibition constant (KI = 0.601 atm), and maximum rate of ethanol (Rmax = 0.172 mmol/L/h at PCO = 0.598 atm) and acetate (Rmax = 0.096 mmol/L/h at PCO = 0.539 atm) production were determined from the applied models.